Deforestation impact on soil organic carbon stocks in Meknes Region, Morocco - amal amal labaioui; Fatima Zahra ( Kbiri Alaoui (African and Mediterranean Agricultural Journal - Al Awamia)
Land-use change affects soil organic carbon (SOC), the depletion of which leads to degradation of soil functions and ecosystem services. Deforestation for agricultural development or expansion is a common land use problem that can cause a range of changes in the ecological environment and soil carbon stocks in cropping systems. The aim of our study was to investigate the variation in organic carbon stocks at 30 cm depth in forest land and adjacent land cleared for crop production in the Meknes region. Geo-referenced composite soils (0 to 30 cm depth) sampled from forest and cultivated cleared land were analysed for SOC. The results showed a reduction in soil carbon stocks of around 25% after deforestation, we found that soil organic carbon stocks decreased significantly (p<0.05) from 4.99 kg/m2 in forest to 3.78 kg/m2 in cropland. We recommend the adoption of sustainable agricultural practices which help to increase the sequestration of atmospheric carbon in soils to maintain high SOC levels or restore depleted SOC stocks.